Finite Element Analysis of a Historic Masonry Building with Unique Architectural Features: A Case of KLP Building at İÜC Cerrahpaşa Campus - Karataş, İhsan Kasım; Yıldızlar, Barış; Sayın, Barış (İstanbul Üniversitesi, 2023)
The walls and slabs of historic masonry buildings, as load-bearing members, tend to lose their strength and durability over time, which can lead to poor seismic performance. Rehabilitation and strengthening practices are performed to protect historic masonry structures and increase their lifespan. On the other hand, before a faithful restoration practice, assessing the seismic performance is important to perform strengthening work during restoration. With this purpose, this study presents a computational approach for seismic performance examination of a historic masonry building with unique architectural features constructed in the early 1930s. The study was composed of two stages; a historical background examination and a computational examination based on numerical analyses. The historical examination includes addressing all functional changes in the building from the construction date to the present. The numerical analyses involved preparing a three-dimensional finite element (FE) model based on the current state of the building and subjecting it to seismic loading. The analysis results revealed that the building is not seismically safe. The study is believed to provide a valuable contribution to the literature by presenting a numerical seismic assessment of the masonry building for consideration in the restoration process.
Keywords: Architecture (Other); Mimarlık (Diğer)